Analysis of some components of water resource management in the sub basin of river Gatuncillo, Panama Canal Watershed - Segura Ramos, Daniel A. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2011